Investigating the effects of the physical working environment upon direct manufacturing workers - Mason, J. P. (Cranfield University, 2005)
Within any developed nation a thriving manufacturing industry is a major driver behind economic prosperity. Key to maintaining a competitive manufacturing capability is the manufacturing system design process and the decisions made within it. The Ford Motor Company manufacturing design teams recognise that key decisions, regarding the physical working environment, can impact upon manufacturing workers, a key resource in maintaining competitiveness. The current problem centres on the lack of confidence among manufacturing system designers, in the tools and guidelines currently available to assess these effects. The working environment can be considered to consist of 'variable' factors (light, noise, temperature, etc.) and 'fixed' factors (equipment layout, hygiene facilities, resting areas, etc.). The aim of the research presented in this thesis, has been to identify the impact of the physical working environment upon manufacturing worker performance. Studies carried out within United Kingdom manufacturing facilities, provided an assessment of the impact of the variable and fixed physical working environment. The variable environmental factors were measured simultaneously against manufacturing worker performance and analysed for any relationships. The fixed environment factors were assessed to see whether their effect upon manufacturing worker motivation could be prioritised within a hierarchy. These studies have provided manufacturing system designers with the ability to make a more confident assessment of the physical working environment and its effect upon manufacturing worker performance. The contribution of this research is therefore, within the context of manufacturing system design, an improved understanding of the effects of the physical working environment upon the performance of manufacturing workers. Specifically, key findings identify the limits in which manufacturing worker performance is not affected by the variable working environment. Also identified, are a set of fixed environmental factors considered to impact the motivation of manufacturing workers. These findings are then used to present manufacturing system designers with a set of guidelines, that can provide assistance with the design of the physical working environment.